Rhizobium etli Produces Nitrous Oxide by Coupling the Assimilatory and Denitrification Pathways - Hidalgo-García, Alba; Torres, María J.; Salas, Ana; Bedmar, Eulogio J.; Girard, Lourdes; Delgado, María J. (Frontiers in Microbiology, 2019)
More than two-thirds of the powerful greenhouse gas nitrous oxide (N2O) emissions from soils can be attributed to microbial denitrification and nitrification processes. Bacterial denitrification reactions are catalyzed by the periplasmic (Nap) or membrane-bound (Nar) nitrate reductases, nitrite reductases (NirK/cd1Nir), nitric oxide reductases (cNor, qNor/ CuANor) and nitrous oxide reductase (Nos) encoded by nap/nar, nir, nor and nos genes, respectively. Rhizobium etli CFN42, the microsymbiont of common bean, is unable to respire nitrate under anoxic conditions and to perform a complete denitrification pathway. This bacterium lacks the nap, nar and nos genes but contains genes encoding NirK and cNor. In this work, we demonstrated that R. etli is able to grow with nitrate as the sole nitrogen source under aerobic and microoxic conditions. Genetic and functional characterization of the assimilatory nitrate reductase enzyme encoded by a gene located in the R. etli chromosome and annotated as narB demonstrated that growth under aerobic or microoxic conditions with nitrate as nitrogen source as well as nitrate reductase activity requires NarB. In addition to be involved in nitrate assimilation, NarB is also required for NO and N2O production by NirK and cNor, respectively, in cells grown microoxically with nitrate as the only N source. Furthermore, β-glucuronidase activity from nirK::uidA and norC::uidA fusions, as well as NorC expression and Nir and Nor activities revealed that expression of nor genes under microoxic conditions also depends on nitrate reduction by NarB. Our results suggest that nitrite produced by NarB from assimilatory nitrate reduction is detoxified by NirK and cNor denitrifying enzymes that convert nitrite into NO which in turn is reduced to N2O, respectively.